Advancing our understanding of urban informality using a multi- actor perspective: The case of Operation Clean Sweep (2013), Johannesburg - Makhetha, Puleng (My University, 2023)
Perspectives on urban informality vary, with some being concerned with the ways in which unserved members of the urban population meet their need for housing or an income, whilst others view it as a failure to plan. However, for the purpose of this research, urban informality was unpacked by considering the political and social aspects of it- to reveal the various actors involved in it and their roles and interests. To achieve this, various sources of literature were consulted, and an analysis of urban informality- in the form informal street trading was conducted using the political and social aspects as a lens. What emanated from this endeavour is a set of actors involved in informal street trading, grouped according to their characteristics. The way they relate to one another- which is fluid based on their interests, was also highlighted. This information on the actors involved in informal street trading was translated into a conceptual framework. Operation Clean Sweep- which is a policy approach employed by the City of Johannesburg in 2013 to manage informal street trading, was used as a case study. To paint a picture of the operation, written accounts on it were considered, which included journal articles, papers from reputable research institutions and journalistic reports. These allowed for the events prior, during and after the operation to be mapped. The accuracy of the information gathered on the operation was corroborated using data triangulation. Once a consistent storyline of the operation had been established, the social and political aspects of urban informality were used as a lens to identify the different actors involved in it. Finally, the conceptual framework developed to map the actors involved in informal street trading was augmented, to include a similar set of actors identified in Operation Clean Sweep. These two sets of actors emanating from literature and those involved in Operation Clean Sweep were juxtaposed and their similarities and differences were noted. The outcomes of the research revealed the prevalence of a multiplicity of actors involved in informal street trading, as captured in literature on informal street trading- and confirmed through an analysis of Operation Clean Sweep. Furthermore, it becomes evident that this myriad of actors have a common interest- despite their heterogeneity and the different roles they assume, which is gaining access to limited prime urban space. The fluid nature of their relationships was also revealed. The outcomes emanating from the study highlight the value of understanding the multifaceted nature of urban informality and the limitations of applying policy approaches in a linear fashion.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Development Planning to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2023